A case of superior segmental optic hypoplasia accompanied by a glaucomatous optic neuropathy - Ikuyo Ohguro (Dove Medical Press, 2008)
Ikuyo Ohguro, Hiroshi OhguroDepartment of Ophthalmology, Sapporo Medical University School of Medicine, Sapporo, Hokkaido, JapanAbstract: This is the first case report of a bilateral superior segmental optic hypoplasia (SSOH) accompanied by a glaucomatous optic neuropathy (GON). A 47-year-old man incidentally diagnosed as having bilateral SSOH, simultaneously disclosed glaucomatous optic disc appearances, including enlargements of the cup of the optic nerve heads and a thinning of the infero-temporal neuroretinal rim with laminar dot sign accompanied by a retinal nerve fiber layer (RNFL) local defect of infero-temporal region in the right eye. The visual field examination revealed that the corresponding nasal step, arcuate scotoma and RNFL field defects in the right eye.Keyword: retinal nerve fiber layer